Nephrostomy tube misplacement in the inferior vena cava following percutaneous nephrostomy - B. G. Guliev; I. A. Povago; A. E. Talyshinsky (Вестник урологии, 2022)
Percutaneous renal interventions are characterized by bleeding and infectious complications, as well as trauma to organs located near the kidney, renal or inferior vena cava (IVC). The article presents a clinical observation of a rare complication of percutaneous nephrostomy (PCN), i.e. migration of the distal end of the nephrostomy tube into the IVC. Its timely removal followed by re-nephrostomy made it possible to avoid bleeding and restore drainage of the pyelocalyceal system. Along with this, the article presents a literature review on this condition in the eLibrary, Springer, MedLine, Embase, UpToDate databases from 2000 to 2021. The indications for PCN, the frequency and risk factors of IVC damage during percutaneous renal interventions, as well as treatment tactics were studied. After the initial evaluation of the literature, ten articles were selected for further analysis. The main risk factors associated with IVC perforation after PCN include the surgeon's lack of experience in instrumental imaging, misjudgment of the length of the nephrostomy tube, and its insertion depth, resulting in its inadequate placement. Removal of the nephrostomy tube from the IVC under radiological and ultrasound guidance or open surgery are the main methods to correct for this complication.